Comparison of upper lip bite test and modified mallampati test for prediction of difficult intubation - Devkota, Kriti; Adhikari, Kiran (Journal of Chitwan Medical College, 2021)
Background: Insertion of endotracheal tube is the basic skill acquired by all anesthesiologists. An unanticipated difficult intubation can be catastrophic and is one of the major causes of morbidity and mortality in anesthetic practice. So, there are multiple screening tests designed to correctly predict difficult intubation but none of them are 100 % accurate. The study aimed to compare the Modified Mallampatti test with Upper Lip Bite test for correct prediction of difficult intubation. Methods: A cross-sectional study was conducted in the College of Medical Sciences, Bharatpur from 16th June 2020 to December 31st 2020. A total of 610 patients requiring general anesthesia with endotracheal intubation were included in the study. The Modified Mallampatti test and Upper Lip Bite test along with laryngoscopy was performed by an experienced anesthesiologist. Sensitivity, specificity, accuracy and positive and negative predictive values for both tests were calculated and compared. Results: The incidence of difficult intubation was 17.7% in our study. The upper lip bite test showed better sensitivity (79.63% vs 37.96%), specificity (93.82% vs 69.92%), positive predictive value (73.5% vs 21.35%), negative predictive value (95.53% vs 83.97%) and accuracy (91.31% vs 64.26%) compared to Modified Mallampatti test Conclusions: Upper lip bite test was a better predictor of difficult intubation compared to MMT with higher accuracy and predictive values.